Altitude training and its influence on physical endurance in swimmers - Strzala, M.; Ostrowski, A.; Szygula, Z (Journal of Human Kinetics, 2011)
It is possible to plan an altitude training (AT) period in such a way that the enhanced physical endurance obtained as a result of adaptation to hypoxia will appear and can be used to improve performance in competition. Yet finding rationales for usage of AT in highly trained swimmers is problematic. In practice AT, in its various forms, is still controversial, and an objective review of research concentrating on the advantages and disadvantages of AT has been presented in several scientific publications, including in no small part the observations of swimmers. The aim of this article is to review the various methods and present both the advantageous and unfavourable physiological changes that occur in athletes as a result of AT. Moreover, AT results in the sport of swimming have been collected. They include an approach towards primary models of altitude/hypoxic training: live high + train high, live high + train low, live low + train high, as well as subsequent methods: Intermittent Hypoxic Exposure (IHE) and Intermittent Hypoxic Training (IHT). Apnoea training, which is descended from freediving, is also mentioned, and which can be used with, or as a substitute for, the well-known IHE or IHT methods. In conclusion, swimmers who train using hypoxia may be among the best-trained athletes, and that even a slight improvement in physical endurance might result in the shortening of a swimming time in a given competition, and the achievement of a personal best, which is hard to obtain by normal training methods, when the personal results of the swimmer have reached a plateau.